Demographic Profile and Childhood Morbidity Pattern in Western Nepal - Adhikari, Jyoti; Belbase, Mohan; Bahl, Lalita (Journal of Nepalgunj Medical College, 2016)
Background: Nepalgunj Medical College is a tertiary care centre in western Nepal. This part of Nepal is under privileged with high rate of illiteracy and poverty leading to various morbidities including pediatric problems. This study is carried out as there have not been many studies with this regard especially from this part of the country. Methods: This is a retrospective study done in patients admitted in pediatric ward of Nepalgunj Medical College, Kohalpur, for six months from June to November 2014. Results: Out of 949 patients admitted in Nepalgunj Medical College, Kohalpur, 604 (63.6%) were male and 345(36.4%) were female. Age range 1-5 years had the maximum number of patients 342(36%) of the total hospital admissions. Respiratory tract infections were the most frequent cause of childhood morbidity 266 (28%) followed by central nervous system illness 138 (14.5%) and gastrointestinal system illness 122(12.9%). Mean hospital stay was 4.3 days. Conclusions: Respiratory tract infections were the most frequent cause of childhood morbidity 266(28%) followed by central nervous system illness 138(14.5%) and gastrointestinal system illness 122(12.9%). JNGMC Vol. 12 No. 2 December 2014, Page: 20-23